ANALISIS PENYIMPANGAN PERILAKU ANAK USIA DINI DALAM KEPEMILIKAN BENDA DI SEKOLAH - Isna Latifah; Prihandoko, Yogi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The concept of ownership is an essential part of moral development that should be introduced from an early age. Children need to learn and understand that everyone has the right to their belongings, and that taking items without permission or asking for money from friends is not appropriate behavior. This study aims to analyze the forms of behavioral deviation related to ownership among early childhood children and to identify the contributing factors and intervention strategies within an early childhood education institution (PAUD). This research uses a qualitative approach with a case study method conducted in several PAUD institutions. Data were collected through observation and interviews. The results indicate that behavioral deviations are linked to a weak understanding of the values of honesty and ownership. Contributing factors include parenting styles, social environmental influences, a lack of moral value reinforcement at school, and economic factors. Effective handling strategies involve educational approaches, rule enforcement, collaboration with parents, the creation of a positive learning environment, and child guidance services. This study highlights the importance of synergy between teachers, parents, and institutions in building children’s moral character from an early age.